High scope approach: learning through action - Mesquita, Cristina (2018)
This chapter analyzes the HighScope curriculum as a preschool pedagogical approach that offers kindergarten teachers a set of ideas and practices supported by the children development, as they value the action of their learning process (Hohmann & Weikart, 2007).